2012
DOI: 10.1038/npp.2011.328
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum and Depression Status are Associated With Lower [11C]raclopride BPND in Reproductive-Age Women

Abstract: The early postpartum period is associated with increased risk for affective and psychotic disorders. Because maternal dopaminergic reward system function is altered with perinatal status, dopaminergic system dysregulation may be an important mechanism of postpartum psychiatric disorders. Subjects included were non-postpartum healthy (n ¼ 13), postpartum healthy (n ¼ 13), nonpostpartum unipolar depressed (n ¼ 10), non-postpartum bipolar depressed (n ¼ 7), postpartum unipolar (n ¼ 13), and postpartum bipolar dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…This decrease in expression of ventral striatal D 2 receptors concurs with the hypoactivity of the mesolimbic dopamine system that is hypothesized to occur in depression, and is also consistent with the decreases in the density of the D 2 receptor found rat models of depression such as learned helplessness, chronic mild stress-induced anhedonia, and the socially-isolated Flinders sensitive line rat [7678]. Although no alterations in the number of D 2 receptors the ventral striatu, of postmortem depressed patients [79], a PET imaging study found lower D 2/3 dopamine receptor density in the striatum of depressed women [80]. Thus, the effects of a reduction of DHA in the brain of the adult rat are consistent with rodent models of depression, and perhaps also with depressed humans.…”
Section: Effects Of N-3 Pufas On Depression-related Neurobiologysupporting
confidence: 66%
“…This decrease in expression of ventral striatal D 2 receptors concurs with the hypoactivity of the mesolimbic dopamine system that is hypothesized to occur in depression, and is also consistent with the decreases in the density of the D 2 receptor found rat models of depression such as learned helplessness, chronic mild stress-induced anhedonia, and the socially-isolated Flinders sensitive line rat [7678]. Although no alterations in the number of D 2 receptors the ventral striatu, of postmortem depressed patients [79], a PET imaging study found lower D 2/3 dopamine receptor density in the striatum of depressed women [80]. Thus, the effects of a reduction of DHA in the brain of the adult rat are consistent with rodent models of depression, and perhaps also with depressed humans.…”
Section: Effects Of N-3 Pufas On Depression-related Neurobiologysupporting
confidence: 66%
“…Increased DA synthesis and release may downregulate D2Rs and decrease subsequent DA synthesis through end product inhibition (Carlsson et al, 1976). Of note, reduced striatal D2R binding has been reported in patients with depression (Moses-Kolko et al, 2012). Although it is unknown whether decreased D2R binding reflects a change in pre-or postsynaptic receptors, both types of receptors are thought to be important in regulation of DA synthesis (Anzalone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several imaging studies of PPD that include subjects with previous MDEs. Changes reported include reduced occipital cortex GABA levels, reduced D 2 receptor binding in the ventral striatum in postpartum irrespective of PPD, and reduced 5-HT 1A receptor binding in the orbitofrontal, subgenual, and mesiotemporal cortex in a sample of unipolar and bipolar PPD (Epperson et al, 2006;Moses-Kolko et al, 2008, 2012. As with many complex psychiatric illnesses, it is generally believed that a number of neuropathological changes contribute to the symptoms of PPD and it is plausible that some of these markers reflect specific vulnerability to PPD, MDE in general, or both conditions.…”
Section: Introductionmentioning
confidence: 99%